2023
DOI: 10.1038/s41467-023-38482-w
|View full text |Cite
|
Sign up to set email alerts
|

A Yap-dependent mechanoregulatory program sustains cell migration for embryo axis assembly

Abstract: The assembly of the embryo’s primary axis is a fundamental landmark for the establishment of the vertebrate body plan. Although the morphogenetic movements directing cell convergence towards the midline have been described extensively, little is known on how gastrulating cells interpret mechanical cues. Yap proteins are well-known transcriptional mechanotransducers, yet their role in gastrulation remains elusive. Here we show that the double knockout of yap and its paralog yap1b in medaka results in an axis as… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 82 publications
(142 reference statements)
0
3
0
Order By: Relevance
“… 88 Furthermore, several studies showed that YAP signaling is required to maintain cellular tension in various cells. 89–92 Interestingly, a recent study found that verteporfin, a YAP inhibitor, 93,94 reduced survivin expression in gastric cancer cells. 95 Thus, YAP might represent a regulator of survivin to modulate cellular tension.…”
Section: Discussionmentioning
confidence: 99%
“… 88 Furthermore, several studies showed that YAP signaling is required to maintain cellular tension in various cells. 89–92 Interestingly, a recent study found that verteporfin, a YAP inhibitor, 93,94 reduced survivin expression in gastric cancer cells. 95 Thus, YAP might represent a regulator of survivin to modulate cellular tension.…”
Section: Discussionmentioning
confidence: 99%
“…This impairment would decrease yap-dependent mechano-transduction, which, in turn, could affect the contraction of the actomyosin network, delaying epiboly progression ( Figure 7 ). In support of this model, the yap mechano-regulatory program seems to be essential for sustaining intracellular tension during gastrulation, that, in turn, controls the assembly of the embryonic A-P axis ( Sousa-Ortega et al, 2023 ). Our simplified model does not take into account other and yet undetermined factors that contribute to this process.…”
Section: Discussionmentioning
confidence: 93%
“…YAP proteins, renowned transcriptional regulators, exhibit nuclear translocation in response to mechanical stimulation, displaying activity in the spreading of cells. , This mechanosensing capability relies on actomyosin contractility, actin capping, severing proteins, and coupling between the ECM and the nuclear envelope. , …”
Section: Intracellular Signaling Pathways Mediating Mechanoregulationmentioning
confidence: 99%